Validation Evidence for the Oviedo Grit Scale (EGO) in a Non-Western Context - Turnalar-Çetinkaya, Neslihan; Çetinkaya, Neslihan Turnalar (My University, 2024)
Grit is a positive non-cognitive characteristic related to perseverance and passion for long-term goals. It positively impacts various aspects of life, but limited tools are available for measuring it, particularly in Turkish. Thus, this research aimed to establish the psychometric values for the Turkish version of the Oviedo Grit (EGO) scale by Postigo et al. (2021). The sample consisted of 500 Turkish university students. The analyses for single items, structural validation, measurement invariance, and the scale’s relationship with personality traits (i.e., big five personality dimensions) and external variables (i.e., grade point average) supported the claim that the EGO scale, originally developed in Spanish by Postigo et al. (2021), is a reliable, unidimensional tool to measure grit Turkish language. Some limitations and potential paths for future research were also discussed.
Keywords: Psikoloji